Perceptions, Preferences and Demographic Profile of Females Regarding Contraception Choices in an Urban Setting - Nazar Muhammad Afridi, Muhammad Ahsan Ali, Ijaz Ali, Muhammad Usman Anjum, Farhan Nazir (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Being a developing country, fertility rates are high in our country while contraception use is sub-optimal. Aim: To assess the factors and perceptions of women of reproductive age influencing their choice of contraceptive method as well as the prevalence of contraception. Duration & place of study: Mohi-ud-Din Islamic Medical College, Mirpur, AJK from January to June 2021 Methods: In this cross-sectional study, females of child-bearing age were selected. They were divided into various groups based on different parameters. Pre-structured and a pre-validated proforma was used to collect data. Results: Most of the females, 74.88%, were between the ages of 21-40 years. Most of the women were literate and 50.51% had completed their matriculation. Majority of them, about 49.69%, have 2-4 children. The working status revealed that 74.95% women were house wives while only 25% were doing a job and 85.06% were Muslims. The proportion of women belonging to low-income group was only 8.76% while the average was almost similar for women belonging to middle- and high-income group. Media exposure was quite high in the study subjects with about 92.60% reported to have had media exposure. Conclusion: There is restricted and reduced use of contraceptive methods among our study subjects. Among those who use contraception, preferred methods are short acting ones.